Maximising benefit and minimising harm of screening - Gray, J A M (BMJ Publishing Group Ltd., 2008)
Gordon Brown has pledged to increase screening services in the NHS. Muir Gray, Julietta Patnick, and Roger Blanks show how experience with the UK breast screening programme can help ensure that they are effective